El modelo de agronegocios en los oasis de Mendoza (Argentina): Notas para una ecosíntesis territorial - Larsimont, Robin Sebastien (2019)
The margins of the oasis of the Mendoza province have acquired in the last two decades special relevance as a focus of investment of the so-called "agribusiness model". The latter has been the protagonist of a real conquestin peripheral areas of the oasis, expanding the agricultural frontier based on the acquisition of land selected for its edaphic characteristics, the exploitation of groundwater and the application of modern irrigation systems.Starring by the so-called new vitiviniculture -characterized by the production of high-quality wine destined for export-, this dynamic was also evident in other fruit or horticultural sectors. Drawing on a triangulation of qualitative data from primary and secondary sources, we explore the ways in which the expansion of the agribusiness model reconfigure the hydrosocial rurality of theses oasis. We analyze these transformations within the framework of a territorial eco-synthesis, arguing that the territoriality of such model acts in a confined, zonal and networked manner.